ANALYSIS AND DEVELOPMENT OF CURRICULUM RELATED TO LEARNING THEORIES: LITERATURE REVIEW - Sari, Filma Alia; Bentri, Alwen; Hidayati, Abna; Rizka, Mifta (Yayasan Amanah Nur Aman, 2025)
The curriculum is the basic structure in education that guides what, how, and why learning takes place. Learning theories provide an important psychological and pedagogical foundation for designing and developing curricula to be more effective and relevant. This article reviews the current literature on the relationship between curriculum analysis and development and learning theories, including behaviorism, cognitivism, constructivism, connectivism, and adult learning theory. The main objective is to evaluate how these theories are integrated into curriculum development, supporting and inhibiting factors, and recommendations for adaptive and innovative curriculum practices. The method used is a systematic literature review of articles from international and national databases from 2010 to 2025. The findings show that although current curriculum construction is largely influenced by constructivism and active learning theory, the application of more formal theories such as behaviorism and connectivism also appears, especially in the context of higher education and online learning. The main obstacles include a lack of understanding of the theory by curriculum designers, limited resources, cultural resistance, and technical challenges. The conclusion states that effective curriculum development requires in-depth contextual analysis, explicit integration of learning theory, stakeholder involvement, and continuous evaluation.